2018
DOI: 10.1093/infdis/jiy480
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Mycobacterium tuberculosis–Strain Infections Are Associated With Poor Treatment Outcomes Among Patients With Newly Diagnosed Tuberculosis, Independent of Pretreatment Heteroresistance

Abstract: Among patients starting first-line tuberculosis therapy in Botswana, mixed infections were associated with poor tuberculosis treatment outcomes, independent of heteroresistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
41
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 43 publications
6
41
1
Order By: Relevance
“…However, as very few of the emergent RAVs were identified even among the multiple low-frequency variants that may represent standing variation or sequencing error(2), it suggests that weekly or more frequent sampling in addition to effective exclusion of sequencing error would be required to identify low-frequency RAVs that were likely to be clinically significant. This is in agreement with another study of treatment failures that found that only variants at >19% frequency were likely to become fixed (14) and that very low-frequency variants did not affect outcome of patients with DS-TB (5).…”
Section: Discussionsupporting
confidence: 92%
“…However, as very few of the emergent RAVs were identified even among the multiple low-frequency variants that may represent standing variation or sequencing error(2), it suggests that weekly or more frequent sampling in addition to effective exclusion of sequencing error would be required to identify low-frequency RAVs that were likely to be clinically significant. This is in agreement with another study of treatment failures that found that only variants at >19% frequency were likely to become fixed (14) and that very low-frequency variants did not affect outcome of patients with DS-TB (5).…”
Section: Discussionsupporting
confidence: 92%
“…However, more recent applications of advanced molecular tools suggest mixed infection might occur more frequently than initially expected (6,7). This possibility led to many research studies of mixed infection, which found that mixed infection is associated with poor treatment outcomes (6,8), including acquisition of multidrug-resistant TB (7,8). Mixed infection research contributed to the discovery that exogenous reinfection was responsible for a substantial portion of incident TB, implying incomplete protection from a primary infection in subsequent infections (9,10).…”
mentioning
confidence: 99%
“…Examining the bases mapped to each site using per-base binomial testing (see Methods) shows sample-C from patient-1 contains multiple mixed positions (M-sites) at the sites differing between A and B. This kind of within-patient heterogeneity, which is reported to be associated with impaired treatment response, 10, 13, 14 is not evident using standard methods of consensus base calling, using which C appears identical to (that is, has a zero pairwise SNV distance from) sample A. Consequently, we decided to develop automated methods detecting mixed TB infection using our routinely sequenced data.…”
Section: Resultsmentioning
confidence: 99%
“…Such infections are currently of clinical interest since response to treatment is known to be delayed in individuals with mixed infection. 10, 13, 14 Mixed infection may reflect either the development of intra-host diversity during chronic infection 6 , or co-infection by more than one strain circulating in the community in which the affected individual resides. 15, 16 Co-circulating strains are commonly closely related, 15 and co-circulation is ongoing in hyperendemic settings, in which mixed isolates are reported in 10-30% of cases.…”
Section: Introductionmentioning
confidence: 99%